1996
DOI: 10.1111/j.1467-6494.1996.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs m Realistic and Unrealistic Control: Assessment and Implications

Abstract: Scales were constructed to measure perceived control over controllable events (realistic control) and perceived control over uncontrollable events (unrealistic control). Internal reliability, test-retest reliability, and discriminant validity of both scales were adequate. Study 1 measured perceived personal control over hassles that judges rated on general controllability. For hassles very high in controllability, perceived personal control was related to belief in realistic control but not to belief in unreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Studies have shown that those persons with a sense of personal or internal control over their illness have better physical and psychological adjustment (Wallston, Malcarne, Flores, Hansdottir, Smith, Stein, et al, 1999). Specifically, a belief in control over one's environment has been related to less subjective pain, better health, and a stronger immune system, as well as a decrease in the destructive effects of ageing (Zuckerman, Knee, Kieffer, Rawsthorne, & Bruce, 1996). Others, however, believe that outside influences strongly dictate their lives and health situations, often leaving them with a sense that they are not entirely in control of their lives.…”
Section: Locus Of Control and Godmentioning
confidence: 97%
“…Studies have shown that those persons with a sense of personal or internal control over their illness have better physical and psychological adjustment (Wallston, Malcarne, Flores, Hansdottir, Smith, Stein, et al, 1999). Specifically, a belief in control over one's environment has been related to less subjective pain, better health, and a stronger immune system, as well as a decrease in the destructive effects of ageing (Zuckerman, Knee, Kieffer, Rawsthorne, & Bruce, 1996). Others, however, believe that outside influences strongly dictate their lives and health situations, often leaving them with a sense that they are not entirely in control of their lives.…”
Section: Locus Of Control and Godmentioning
confidence: 97%
“…On the other hand, several authors have pointed out the adverse consequences of high perceived control in circumstances where control is not possible (Burger, 1989;Thompson, 1993;Thompson, Cheek, & Graham, 1988;Whyte, Saks, & Hook, 1997). Wannon (1990) and Zuckerman, Knee, Kieffer, Rawsthorne, and Bruce (1996) have drawn an important distinction between realistic and unrealistic control beliefs. Realistic control beliefs concern circumstances where control is objectively possible.…”
Section: Is High Perceived Control Adaptive or Maladaptive?mentioning
confidence: 99%
“…It is worth recalling Wannon's (Zuckerman, Knee, Kieffer, Rawsthorne, & Bruce, 1996) differentiation between realistic and unrealistic control where the former refers to control over controllable situations and the latter concerns events that are genuinely out of one's control. Wannon showed that high realistic and low unrealistic control facilitated pupils' achievement at school, better adapted to school requirements and increasing empathy and competent problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…Wannon showed that high realistic and low unrealistic control facilitated pupils' achievement at school, better adapted to school requirements and increasing empathy and competent problem-solving. Zuckerman, Knee, Kieffer, Rawsthorne, and Bruce (1996) showed that people with chronic unrealistic control were prone to repetition, thereby, losing time. Wortman and Brehm (1975) asserted that in really uncontrollable situations, emotion-focused coping functions are more effectively than problem-focused coping.…”
Section: Discussionmentioning
confidence: 99%